Polycyclic Aromatic Hydrocarbons in Surface Water from Wuhai and Lingwu Sections of the Yellow River: Concentrations, Sources, and Ecological Risk - Yun Liu; Qingwei Bu; Hongmei Cao; Handan Zhang; Chuansheng Liu; Xiaofan He; Mengqi Yun (Journal of Chemistry)
In this study, concentrations, sources, and ecological risk of 16 polycyclic aromatic hydrocarbons (PAHs) in 41 surface water samples collected from Wuhai and Lingwu sections of the Yellow River were investigated. The results showed that total PAH concentrations varied from 27.5 ng/L to 234 ng/L and from 135 ng/L to 265 ng/L in surface water of Wuhai and Lingwu sections, respectively. Source identification was performed by using principal component and multiple linear regression analysis. PAHs in Wuhai section of the Yellow River were mainly from coal combustion (35%) and vehicle exhausts (34%). Ecological risk of PAHs to aquatic organisms was assessed by applying the probabilistic risk assessment method. The results showed that the probabilities of exceeding the chronic toxicity for 5% of the species were 28% and 32% for PAHs in surface water from Wuhai and Lingwu sections, respectively. It has been demonstrated that there is an urgent need for environmental managers to take measures to reduce the ecological risk of PAHs in the aquatic environment in both Wuhai and Lingwu sections of the Yellow River.